EFFECT OF NATURE SOUNDS MUSIC THERAPY DURATION ON BLOOD PRESSURE AMONG PRIMIPAROUS POSTPARTUM WOMEN - Yulinda Laska; Erika Fariningsih; Sherly Mutiara (International Journal of Social Science, 2021)
Background: Postpartum blues rate for Asia is between 26-85%, while the prevalence in Indonesia is 50-70%. All postpartum women can experience stress, almost 80% of primiparous women experience feelings of sadness after childbirth. Stress can stimulate the sympathetic nerves to trigger the work of the heart and can trigger increased blood pressure. Music raises changes in brainwave status, stress hormones and affects the cardiovascular system. Nature sounds music is music that has a slow tempo and may cause relaxed and comfortable feelings. Objective: To prove the effect of natural music therapy duration on blood pressure among primiparous postpartum women. Method: This study used a true experimental design (pretest-posttest control group design). The sampling technique used Simple random sampling. The respondents of this study were primiparous postpartum women amounted to 39 mothers. The samples in this study were divided into three groups namely the treatment group of music therapy with 15 minutes duration, the treatment group of music therapy with 30 minutes duration and the control group. Analysis to test the effect of duration of nature sounds music on primiparous postpartum women used One-way ANOVA and Kruskall Wallis test Results: The result of study analysis showed that there was differences between systolic blood pressure and diastolic blood pressure with p-value 0,010 and 0,009 (p value <0,05) Conclusion: There was an effect of duration of natural music therapy on blood pressure